2017
DOI: 10.1080/16546628.2017.1369343
|View full text |Cite
|
Sign up to set email alerts
|

Non-digestible stachyose promotes bioavailability of genistein through inhibiting intestinal degradation and first-pass metabolism of genistein in mice

Abstract: This study was designed to explore the molecular mechanism of stachyose in enhancing the gastrointestinal stability and absorption of soybean genistein in mice. Male Kunming mice in each group (n = 8) were administered by intragastric gavage with saline, stachyose (250 mg/kg·bw), genistein (100 mg/kg·bw), and stachyose (50, 250, and 500 mg/kg·bw) together with genistein (100 mg/kg·bw) for 4 consecutive weeks, respectively, and then their urine, feces, blood, gut, and liver were collected. UPLC-qTOF/MS analysis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

2
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 33 publications
1
11
0
Order By: Relevance
“…Vaporization heater and capillary heater were maintained at 100°C and 300°C, respectively. The analysis was carried out by following the methoof Lu et al (25) with slight modifications. Briefly, analysis was conducted in the scan mode (m/z) from 100 to 1,000 in selected ion monitoring mode of negative (m/z) 464 for isoquercetin, (m/z) 306 for epigallocatechin, (m/z) 168 for dihydroxyphenylacetic acid, (m/z) 290 for catechin, (m/z) 194 for ferulic acid, (m/z) 288 for epicatechin, (m/z) 169 for gallic acid, (m/z) 286 for kaempferol, (m/z) 301 for quercetin and (m/z) 609 for rutin.…”
Section: Methodsmentioning
confidence: 99%
“…Vaporization heater and capillary heater were maintained at 100°C and 300°C, respectively. The analysis was carried out by following the methoof Lu et al (25) with slight modifications. Briefly, analysis was conducted in the scan mode (m/z) from 100 to 1,000 in selected ion monitoring mode of negative (m/z) 464 for isoquercetin, (m/z) 306 for epigallocatechin, (m/z) 168 for dihydroxyphenylacetic acid, (m/z) 290 for catechin, (m/z) 194 for ferulic acid, (m/z) 288 for epicatechin, (m/z) 169 for gallic acid, (m/z) 286 for kaempferol, (m/z) 301 for quercetin and (m/z) 609 for rutin.…”
Section: Methodsmentioning
confidence: 99%
“…As a classic prebiotic, Sta has been proven to promote the growth of beneficial intestinal bacteria, inhibit pathogenic bacteria, and improve glucose metabolism (Liu et al, 2019;Liang et al, 2020). Moreover, Sta enhances the absorption of soybean genistein and tea polyphenols in mice (Li et al, 2016;Lu et al, 2017). Therefore, we hypothesized that Sta improves the actions of BBR on glucose homeostasis by regulating intestinal microbiota.…”
Section: Introductionmentioning
confidence: 99%
“…Owing to its structural similarity to endogenous estrogen 17 estradiol, Genistein is also called phytoestrogens and could bind with estrogen receptor and activate its downstream signaling pathway 14, 15. Lu et al found when the mice were administrated with genistein at 100 mg/kg, the serum concentrations of genistein was at an average of approximately 60 ng/ml, and stachyose could enhance the absorption of genistein in mice 16. Genistein was shown to be a potent inhibitor of the tyrosine-specific protein kinase RET , and has been used for clinical treatment of prostate carcinoma and non-small cell lung cancer 17-22.…”
Section: Introductionmentioning
confidence: 99%